Penerapan Kompres Hangat Untuk Menurunkan Demam Pada Anak Dengan Demem Berdarah Dengue - Grace Rehulina; IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Dengue hemorrhagic fever is a disease that attacks children and adults caused by the dengue virus. The aim of implementing nursing care for dengue hemorrhagic fever patients who experience an increase in body temperature begins with a comprehensive nursing approach. This research method uses descriptive research methods with case studies and literature studies. Nursing care was provided to an 18 year old boy. The results of the assessment showed seven nursing problems, namely ineffective airway clearance, hyperthermia, risk of bleeding, risk of hypovolemia, risk of nutritional deficit, constipation and risk of infection. The implementation carried out was applying warm compresses with a duration of 10-15 minutes for 2 days during fever to reduce the patient's body temperature. The evaluation results showed that there was a continuous decrease in body temperature from 38.6oC to 36.5oC on the second day and the results accelerated the process of reducing fever in children. In conclusion, warm compresses can be applied to dengue hemorrhagic fever patients to reduce fever. The application of Evidence Based Nursing in providing nursing care is very appropriate to apply to patients to improve the quality of evidence-based nursing care. It is hoped that the results of this research can provide information for hospitals and educational institutions about nursing care.